The η1-H–C⋯Hg agostic interactions in the mercury complexes of N-confused porphyrin. Issue 41 (8th October 2018) - Chen, Yi-Chun; Tung, Jo-Yu; Liu, Ta-Kang; Tsai, Wei-Joe; Lin, Hsiang-Yin; Chang, Yu-Chang; Chen, Jyh-Horung
Abstract : The bond path for the η 1 -H(17)–C(17)⋯Hg agostic interactions in4–9 was a through-space interaction [Hg⋯C(17)] and a through-bond interaction [Hg⋯H(17)]. Abstract : Six four-coordinated complexes of the chemical formulae [Hg(2-N CH2 COOCH2 CH3 -21-H-NCTPP)X] with X = Cl (5 ), Br (6 ), I (7 ), [Hg(2-NCH3 -21-H-NCTPP)Cl] (4 ) and [Hg(2-NCH2 COOCH2 C6 H5 -21-H-NCTPP)X] with X = Cl (8 ), I (9 ) are synthesized and structurally determined. The bond path for the weak η 1 -H(17)–C(17)⋯Hg agostic interactions between the Hg center and H(17) in complexes4–9 was a through-space interaction from Hg to agostic carbon [C(17)] followed by a through-bond interaction from C(17) to an agostic proton [H(17)]. The magnitude of J [Hg–H(17)] [or the agostic upfield shift Δ δ ago of the C(17)] for these complexes increases as the halide ligand varies from iodide to chloride, ranging from 33.2 Hz (or 14.3 ppm) for I − to 36 Hz (or 15.8 ppm) for Br − and 36.9 Hz (or 16.0 ppm) for Cl − . The plot of J [Hg–H(17)] for the agostic proton H(17) versus |Δ δ ago | for the agostic carbon atom C(17) in compounds3–9 was linearly expressed as J [Hg–H(17)] = 2.29 |Δ δ ago | + 0.13.